Risk-taking, Temper, and Impulsivity: An Investigation on the Effects of Dimensions of Self-control on Adolescent Violent and Minor Delinquency - McLeod, Lauren (2018)
The current study explores potential disaggregated, simultaneous, and interactive effects of a composite scale measure of self-control on self-reported adolescent violent delinquency and minor delinquency. Using data from 616 Dutch adolescents participating in the Study of Peers, Activities, and Neighborhoods (SPAN), this exploratory study seeks to investigate the full utility of the self-control measure and its effect on adolescent delinquency. Specifically, this thesis explores if a composite measure of self-control—along with corresponding disaggregated measures—significantly predicts violent and minor delinquency independently from and simultaneously with one another. Interaction effects are also investigated with exploratory analysis. Using negative binomial regression, results indicated that self-control significantly predicted both adolescent violent delinquency and minor delinquency when examined as a composite measure and disaggregated into dimensional measures. Results further indicated that in simultaneous models, all dimensional measures of self-control significantly predicted violent delinquency; however, risk-taking was the only significant predictor of minor delinquency. This would suggest that dimensional measures of self-control influence varying types of delinquency differently which is inconsistent with the theory of self-control. Contributing preliminary findings to the self-control literature, impulsivity was found to moderate the relationship between risk-taking and minor delinquency in a longitudinal analysis. This suggests that the effect of risk-taking on minor delinquency does vary across levels of impulsivity and future research should investigate this finding further in other samples. This thesis argues that composite scale measures of self-control should be disaggregated to better understand how individual dimensions of self-control influence different forms of delinquency